TRANSFORMING WIRELESS COMMUNICATION INTO NEXT-GEN: THE ROLE OF AI & TERAHERTZ WAVES IN 6G NETWORKING - Ayesha Rashid; Muhammad Shahid Javed; Ali Irtaza; Muhammad Azeem (Spectrum of Engineering Sciences, 2025)
The approaching technology launch in the world is called the sixth generation (6G networking system of newly invented wireless communication system. It is expected to be operational between 2027 and 2030. This new 6G wireless technology is expected to set new trends in human and machine interaction with ultra-fast facelifted data transmission speed with almost zero latency in communication. This research paper has tried to explore the potential of AI-based 6G networks’ potential. It also sheds light on major technologies added to make it efficient, for example, Artificial Intelligence (AI), Machine Learning (ML), Terahertz (THz), and Green Effects. A next-generation 6G technology is predictable to reveal new horizons and help to run new applications of holograph communications. This research also explores significant challenges posed by this new technology, for example, safety and vigor competence. The main conclusions of this inquiry are that it finds gaps in 5G and fills the gap and suggests that the gap may be filled by the development of 5G, which is possible by adding devices in 5G systems. These devices and new functions would upgrade 5G into 6G. Moreover, this research focuses on the role of edge computing, IoT integration and security measures. This paper sums up by explaining that real-world applications, for example, smart cities, innovative healthcare and automatic vehicles, are going to launch along with fewer issues in space communication and privacy in 6G technology. Keywords (AI, wireless, Terahertz, AI-driven, Holographs).